The Epidemiology of Dementia and Alzheimer Disease in Portugal: Estimations of Prevalence and Treatment-Costs - Santana, Isabel (2015)
Introduction: The incidence and prevalence of global dementia and Alzheimer’s disease (AD) increase with age, almost doubling every five years after the sixth decade of life. Demographic aging is a reality in Portugal, being expectable that the number of dementia cases also increases. Even so, dementia-epidemiological data in Portugal is scarce and cost-of-illness studies are almost inexistent. Our aims were to obtain up-to-date information about the prevalence of dementia/ Alzheimer’s disease in Portugal, to estimate thenumber of cases effectively diagnosed as Alzheimer’s disease and to determine illness-costs with specific dementia treatment.Material and Methods: The numbers of age-adjusted prevalence of dementia obtained for Occidental Europe (Alzheimer’s Disease International study), where applied to the resident population in Portugal (2013). Estimations related to diagnosis and treatment-costs were based in data provided by the Intercontinental Marketing Services Health (IMSH) – 2013.Results: The estimated number of Portuguese people with dementia among those aged ≥ 60 years, is 160287, representing 5.91% of this population-stratum. Knowing Alzheimer’s disease is responsible for 50-70% of all cases, we might conclude there are between 80144 and 112201 patients. According to IMSH-data, 76250 receive anti-dementia drugs and the costs of this kind of medication is 37 M€/year.Conclusions: As a consequence of the demographic aging, also the number of dementia cases increases. Aparentely, not all Alzheimer’s disease patients receive the recommended medication, suggesting this condition is still under-diagnosed. However, figures indicate a positive progression with an increment of treated cases and a reduction of medication-costs.